Cognitive Dysfunction in Hospitalized Patient with Moderate-to-Severe COVID-19: A 1-Year Prospective Observational Study - Vasile MC; Vasile CI; Arbune AA; Nechifor A; Arbune M (Journal of Multidisciplinary Healthcare, 2023)
Mihaela-Camelia Vasile,1,2,* Claudiu-Ionut Vasile,2,3,* Anca-Adriana Arbune,4,5,* Alexandru Nechifor,1,* Manuela Arbune1,6,* 1Clinical Medical Department, Medicine and Pharmacy Faculty, “Dunărea de Jos” University, Galati, Romania; 2Infectious Diseases Department II, Clinic Hospital for Infectious Diseases, Galati, Romania; 3Psychiatry Department I, Clinic Psychiatry Hospital, Galati, Romania; 4Neurology Department, Fundeni Clinical Institute, Bucharest, Romania; 5Multidisciplinary Integrated Center of Dermatological Interface Research (MIC-DIR), “Dunărea de Jos” University, Galați, Romania; 6Infectious Diseases Department I, Clinic Hospital for Infectious Diseases, Galati, Romania*These authors contributed equally to this workCorrespondence: Claudiu-Ionut Vasile, Email vasilemclaudiu@yahoo.comPurpose: To screen the neurocognitive impairment persistent post-COVID-19.Patients and Methods: We assessed the neuropsychiatric disorders associated with COVID-19 in a prospective study, by “Mini-Mental State Examination” (MMSE) and Montreal Cognitive Assessment (MoCA) questionnaires, applied in the discharge to COVID-19 hospitalized patients for moderate and severe forms of disease. They were followed-up in 6 and 12 months.Results: The tests were performed in the baseline and were reevaluated after 6 and 12 months. Baseline cognitive dysfunction was found in 12.4% of patients, according to the MMSE test and in 19.7% by the MoCA scores. Overall cognitive dysfunction in COVID-19 was returned to normal after 6 months, although some tasks are more severe and persistently impaired, such as attention, concentration, short memory, and execution skills. The male gender and the degree of hypoxia, related to the severity of COVID-19 infection, were related to cognitive dysfunction in the study group.Conclusion: Cognitive domain impairments related to COVID-19 could persist over 6 months post-acute infectious episode requiring systematic screening for early diagnosis of progressive brain pathologies and rehabilitation. Keywords: mental health, MoCA test, MMSE test, cognitive domains, COVID-19